Microstructural properties of glass composite material made from incinerated scheduled waste slag and soda lime silicate (SLS) waste glass - Juoi, J.M.; Arudra, D.; Rosli, Z.M.; Hussain, K.; Japper Jaafar , A (Elservier, 2013)
Glass composite material (GCM) was produced from incinerated scheduled waste bottom slag (BS) and soda lime silicate (SLS) waste glass. The effect of BS waste loading on the GCM and the microstructural properties was studied. Batches of powder mixture is formulated with 30 wt.% to 70 wt.% of BS powder and SLS waste glass powder for GCM sintering. The powder mixtures of BS and SLS waste glass were compacted by uniaxial pressing method and sintered at 800 °C with heating rate of 2 °C/min and one hour soaking time. The phases identified by X-ray diffraction (XRD) method in all sintered samples are anorthite sodian, quartz, hematite and diopside. It was observed that higher BS waste loading results in higher porosity, higher water absorption and lower bulk density according to ASTM C373. In contrast, the Vickers microhardness value determined according to ASTM C1327, decreases with higher BS waste loading. This similar trend is observed for modulus of rupture (MOR) analysis which was performed according to ISO 10545-4. This physical and mechanical properties can be related to the microstructure observed during scanning electron microscope (SEM) analysis. More open pores and less dense surface are observed for higher BS waste loading samples. On the other hand, samples with lower BS waste loading consists of higher dense surface and no open pores. GCM with batch formulation of 30 wt.% BS and 70 wt.% SLS waste glass has shown the lowest water absorption percentage of 1.17%, the lowest porosity percentage of 2.2% and the highest bulk density value of 1.88 g/cm3. It also shows the highest MOR of 70.57 MPa and 5.6 GPa for Vickers microhardness with congruent microstructure features.